Implementation of Thematic Songs in Stimulating Early English Vocabulary in Children - Safilaha , Noviana Aliya As; Astuti, Willi (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the application of thematic songs in the development of English vocabulary related to rainbow colors in early childhood. The author chose this topic because of the lack of English vocabulary mastery in children, especially in recognizing colors. The methods used in this study were observation of children, interviews with teachers and parents, and documentation of learning activities. The research subjects were children aged 4-5 years. The results showed that singing songs was an effective method for increasing children's vocabulary, as the rhythm and melody made it easier for children to remember new words such as